2010
DOI: 10.1016/j.ultsonch.2009.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ultrasound for the destruction of Mycobacterium sp. strain (6PY1)

Abstract: Ultrasound is widely used to disinfect drinking water and wastewater due to its strong physical and chemical effects on microorganisms. The aim of this study was to investigate the effect of ultrasound on the destruction of Mycobacterium strain 6PY1. Ultrasound waves (20 kHz or 612 kHz) were used to treat aqueous suspensions of Mycobacterium at different volumes, initial bacterial concentrations, and power densities. At the same power density and the same exposure time, sonication at high frequency resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Our results indicated that the killing rate was independent of the initial bacterial number. Al Bsoul et al investigated the effect of initial cell concentrations on the destruction process and also found no significant effect on the disinfection rate (36). It was possible that with a higher bacterial density, the mechanical and chemical energy generated by ultrasonic waves could act on a higher proportion of bacteria.…”
Section: Enumeration Of Surviving Cells By Plate Counts (Cultivability)mentioning
confidence: 99%
“…Our results indicated that the killing rate was independent of the initial bacterial number. Al Bsoul et al investigated the effect of initial cell concentrations on the destruction process and also found no significant effect on the disinfection rate (36). It was possible that with a higher bacterial density, the mechanical and chemical energy generated by ultrasonic waves could act on a higher proportion of bacteria.…”
Section: Enumeration Of Surviving Cells By Plate Counts (Cultivability)mentioning
confidence: 99%
“…6c. Increasing US power results in higher particle breakage [64] and more efficient removal, in the high frequencies [59,60]. In our system, decreasing the power from 20 to 10 W, and consequently, the power-to-volume ratio, decreased the efficiency, although in a non-linear, cost-effective manner; 50% reduction did not result to 50% decrease of the inactivation, but to 33%, although the main target is total inactivation.…”
Section: Fenton and Sonication Factorsmentioning
confidence: 65%
“…Finally, although literature suggests that modifying the sonication volume has not a significant effect on the efficiency of the sonication process (if the power-to volume ratio is respected) for bacterial inactivation [59,60], in Fig. 4c we observe 2 and 3 log 10 U of difference, respectively.…”
Section: Hydraulic Parametersmentioning
confidence: 76%
“…Air bubbles are generated and they liberate a variable amount of energy when collapse, causing damage to the cell structure. Furthermore, highly reactive radicals, such as ·OH and ·H, are formed inside the bubbles are released to the medium, attacking the microorganism structure and causing cell death [25].…”
Section: Alternatives To Prevent Microbial Growthmentioning
confidence: 99%